A magnesium alloy powder for additive manufacturing of degradable medical implants and its preparation method and application

By adding specific elements and introducing MgMoO4 particles into the magnesium alloy, a molybdate protective film is formed, which solves the problem of excessive degradation rate of magnesium alloy implant materials and achieves improvement in the mechanical properties of the implant and regulation of the degradation rate.

CN118895445BActive Publication Date: 2025-01-21SHANDONG HAIHUA GRP CO LTD +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411385114.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-21
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

The degradation rate of existing magnesium alloy implant materials in the human body is too fast, resulting in the loss of structural integrity and mechanical support, and it is easy to cause an increase in subcutaneous airbags and local pH values, hindering bone tissue healing.

Method used

By adding 0.5% to 2% Ca, 0.1% to 0.5% Zn, 0.1% to 0.35% Cu and 0.01% to 0.05% Mo into the magnesium alloy, and using a laser selective melting process to introduce high thermal stability MgMoO4 particles to form a molybdate precipitant protective film to regulate the degradation rate and mechanical properties of magnesium alloys.

Benefits of technology

The degradation rate control of magnesium alloy implant materials is achieved, extending the effective life of the implant, improving its mechanical properties and antibacterial function, while avoiding the problems of premature structural damage and local pH increase.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118895445B_ABST
    Figure CN118895445B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of biomedical materials, and specifically relates to a magnesium alloy powder for additive manufacturing of degradable medical implants and a preparation method and application thereof. The magnesium alloy powder is composed of MgCa x Zn y Cu z Particles and attached to MgCa x Zn y Cu z The composition of MgMoO4 particles on the particle surface is, by weight percentage, 0.5≤x≤2%, 0.1≤y≤0.5%, 0.1≤z≤0.35%, the remainder is Mg, and MgMoO4 accounts for MgCa x Zn y Cu z The present invention utilizes high-pressure argon gas to carry MgMoO4 particles in gas-solid two-phase flow atomization to obtain spherical magnesium alloy powder with MgMoO4 particles attached to the surface, and the medical magnesium alloy implant obtained by laser selective melting process can achieve the organic combination of adjustable strength and degradation rate, good biocompatibility and antibacterial properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of biomedical materials, and specifically relates to a magnesium alloy powder for additively manufacturing a degradable medical implant, and a preparation method and application thereof. Background Art

[0002] Additive Manufacturing (AM) technology is a new manufacturing technology based on the principle of layered manufacturing, which uses the method of material accumulation layer by layer to directly manufacture digital models into physical parts. The laser selective melting (SLM) technology in additive manufacturing uses a high-energy laser to melt a thin layer of powder (usually 20 to 50 μm thick), and forms high-density components of any complex shape based on the method of fine powder laying layer by layer on the powder bed and laser melting and accumulation layer by layer. The forming accuracy is high. For implants with complex shapes such as the jaw, pelvis and coronary stents, μ-CT scanning of different patients and defect sites can be used to obtain three-dimensional data models, thereby preparing complex bionic structures and achieving personalized customization.

[0003] Currently, implantable devices used in clinical medicine are mainly made of inert materials, such as titanium-based materials, which have become the most important metal materials. Magnesium (Mg) is a degradable metal with excellent biocompatibility and mechanical properties similar to those of bones. 2+ It can be metabolized by the kidneys and excreted from the body through urine without cumulative effects. It is considered to be a revolutionary implant material with great development potential. As an essential nutrient for the human body, magnesium not only participates in the synthesis of more than 600 enzymes, but also improves the stability of insulin in the human body, promotes normal carbohydrate metabolism, and reduces the incidence of coronary heart disease and hypertension; as a cardiovascular stent, it can effectively improve myocardial blood supply; as a bone implant material, it can not only effectively heal bone tissue damage (injury), relieve patients' pain, but also improve patients' quality of life. However, the standard electrode potential of magnesium (-2.37V) is low, and it is not suitable for the human body rich in Cl. -In tissue fluid, magnesium alloys are prone to electrochemical corrosion. The high degradation rate causes the effective service life of magnesium alloys in the human body to be far lower than the time required for bone tissue healing (3 to 6 months), causing the implant material to lose its structural integrity and mechanical support prematurely and fail prematurely. At the same time, magnesium alloys will produce excessive H2 during the self-degradation process in the human body to form subcutaneous air bags, causing the local pH value of the blood to increase, hindering the normal healing of bone tissue. As a medical implant material, magnesium alloys must consider the following aspects: First, biocompatibility and biosafety, alloying elements must use non-toxic elements; second, good mechanical properties, as an orthopedic implant material, the yield strength should be greater than 200 MPa, the elongation should be not less than 10%, and the degradation rate in simulated body fluid (SBF) at 37°C should be less than 0.5 mm / year to ensure that the effective "life" of the implant is 90 to 180 days; third, controllable biodegradation, most magnesium alloys are susceptible to local corrosion, and uniform and controllable degradation is essential for accurately predicting the "life expectancy" of implants. The Chinese patent document with the publication number CN 114231811 A discloses a Mg-Nd-Zr-Sr-Sc-Sm biodegradable magnesium alloy and its preparation method, which is composed of the following components: Nd: 4% to 5%, Zr: 1% to 1.5%, Sr: 2% to 2.5%, Sc: 1.2% to 2%, Sm: 0.8% to 2.8%, and the rest is Mg, and the mechanical properties and corrosion resistance of the magnesium alloy are improved by adding heavy metal rare earth elements. However, there are relatively few studies on rare earth elements at present, and some rare earth elements have toxic side effects on the human body, such as heavy metal rare earth elements such as neodymium (Nd), samarium (Sm), and europium (Eu). Therefore, how to effectively regulate the degradation rate of magnesium alloy implant materials, while achieving the matching of magnesium alloy implant materials with the mechanical behavior of natural bone tissue and having excellent biocompatibility, antibacterial and other biological functions, is a problem that needs to be solved urgently. Summary of the invention

[0004] The primary purpose of the present invention is to provide a magnesium alloy powder for additive manufacturing of degradable medical implants.

[0005] To achieve the above object, the technical solution of the present invention is:

[0006] A magnesium alloy powder for additive manufacturing of degradable medical implants, the magnesium alloy powder is composed of MgCa x Zn y Cu z Particles and attached to MgCa x Zn y Cu zThe composition of MgMoO4 particles on the particle surface is, by weight percentage, 0.5%≤x≤2%, 0.1%≤y≤0.5%, 0.1%≤z≤0.35%, the remainder is Mg, and MgMoO4 accounts for MgCa x Zn y Cu z 0.02% to 0.1% by weight. x Zn y Cu z The particles are spherical with a particle size of 13~52μm, and the MgMoO4 particles are spherical with a particle size of 1~3μm.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned magnesium alloy powder for additive manufacturing of degradable medical implants, comprising the following steps:

[0008] (1) According to MgCa x Zn y Cu z Weigh the raw materials magnesium block, zinc block, calcium block and copper wire in corresponding proportions according to the weight percentage of each component of the alloy, put them into an induction melting furnace, and melt them under the protection of Ar gas to obtain an alloy melt;

[0009] (2) pouring the alloy melt obtained in step (1) into a tundish with a φ5 mm leak hole at the bottom through a guide tube under the protection of Ar gas, and simultaneously starting high-pressure argon gas to carry MgMoO4 particles and spray them out from the annular gap of the atomizer nozzle, and subjecting the alloy melt flowing out of the leak hole of the tundish to gas-solid two-phase flow atomization to obtain spherical magnesium alloy powder with MgMoO4 particles attached to the surface, namely, magnesium alloy powder for additive manufacturing of degradable medical implants;

[0010] Furthermore, the pressure range of the protective gas Ar in step (1) is 1.0-1.2×10 5 Pa, the melting temperature range is 680~750℃.

[0011] Furthermore, in step (2), the pressure range of argon gas is 1-3 MPa, and the flow rate of argon gas is 3-6.5 m / s. 3 / min; the MgMoO4 particle flow rate is 1.4~3.8mg / s, and the particle size is 1~3μm; the atomization time is 30~40min, and the atomizer used is a tightly coupled annular gap nozzle with an annular gap width of 3mm.

[0012] Another object of the present invention is to provide a use of magnesium alloy powder for additive manufacturing of degradable medical implants, wherein the magnesium alloy powder is used in the laser selective melting process in additive manufacturing to prepare degradable medical implants. The degradable medical implants include: bone nails, bone plates, bone filling devices, vascular stents, bile duct stents, urethral stents, and tracheal stents. In the laser selective melting process, the laser power is 150-400W, the laser spot diameter is 40μm-70μm, the scanning speed is 250-500mm / s, the layer thickness is 15-25μm, the scanning spacing is 40-70μm, and the inter-layer rotation angle is 67°; the yield strength of the magnesium alloy sample obtained by the laser selective melting process is 235MPa-268MPa, and the elongation is 13.5%-21.4%; when the magnesium alloy is immersed in SBF simulated body fluid, it "self-secretes" MoO4 2- The ions are deposited on the surface of the sample to form a protective film to achieve "self-healing", effectively inhibiting the corrosion of the magnesium alloy sample, with an average corrosion rate of 0.1~0.4mm / y in 28 days. By designing and adjusting the magnesium alloy components and precipitants, an organic combination of strength and corrosion resistance can be obtained, thereby achieving the regulation of the degradation behavior of medical magnesium alloy implants.

[0013] Compared with the prior art, the present invention has the following advantages:

[0014] Molybdenum (Mo) is a chemically stable metal with remarkable corrosion resistance. It exhibits excellent corrosion resistance and high stability in neutral medium, acidic medium, especially strong oxidizing acid medium, and alkaline medium, especially alkaline medium at high temperature. Based on the bionic principle that snails can secrete mucus to repair themselves when injured, the present invention introduces water-soluble MgMoO4 into magnesium alloy. When body fluid contacts magnesium alloy and causes corrosion of magnesium alloy, MoO4 2- The ions will be released and enriched on the surface of the magnesium alloy to form a uniform, dense and stable molybdate precipitant protective film, thereby effectively preventing further corrosion of the magnesium alloy and achieving "self-healing". The sterilization history of copper ions is very long. The magnesium-copper alloy prepared by adding an appropriate amount of copper to magnesium will be degraded due to the Cu 2+ The dissolution of molybdate ions shows obvious antibacterial function. In animal experiments, it shows strong anti-infection and certain biological functions of promoting osteogenesis. When the copper mass ratio in magnesium alloy is 0.1%~0.35%, it has strong anti-infection performance. In addition, due to the presence of a uniform, dense and stable molybdate precipitant protective film on the surface of magnesium alloy, it hinders the dissolution of Cu ions. 2+ ions continue to dissolve, thereby controlling Cu 2+The rate of entering the human body. Ca is one of the important elements necessary for the human body. The content of Ca required for the human body to ingest every day is about 1000~1200 mg. It is a basic element for bone development. It can not only promote the proliferation and differentiation of bone cells, but also combine with bone tissue to induce bone regeneration. It has good biocompatibility and is non-toxic to cells. It can be used as a clinical medical implant material. Zn and Ca elements show similar biocompatibility. When the weight percentage of Zn and Ca in magnesium alloy does not exceed 5%, they are non-toxic to cells and have a promoting effect on cell vitality to a certain extent. It can regulate the activity of human cells, and the release of an appropriate amount of zinc ions can promote cell proliferation and differentiation of bone cells. Molybdenum is a very important nutrient for animals and plants, and has the characteristics of good biocompatibility. The magnesium alloy of the present invention contains a trace amount of molybdenum of 0.01%~0.05%, which enhances the corrosion resistance of the magnesium alloy without producing cytotoxicity. Adding an appropriate amount of Ca element to the medical magnesium alloy can refine the grains, thereby improving the microstructure of the magnesium alloy, and improving its mechanical properties and corrosion resistance. After adding a certain amount of Zn to medical magnesium alloy, it can refine the grains, thereby improving the strength and elongation of the alloy. Zn element has a strong solid solution strengthening effect while refining the grains, which can enhance the mechanical properties of magnesium alloy. Cu element has a strengthening effect on magnesium alloy. Ultrafine MgMoO4 with high melting point is introduced into magnesium alloy by high-speed gas-solid two-phase flow impacting magnesium melt. It contacts with magnesium matrix with a clean interface, which enhances the strength and toughness of magnesium alloy. Laser selective melting has the characteristics of high cooling rate, which can obtain fine microstructure. The cooling rate of Mg alloy in SLM process can reach 1×10 6 K.s -1 Therefore, the microstructure of SLM-formed Mg alloy has finer grains, making its performance more advantageous than that of traditional casting. Therefore, the synergistic effect of grain refinement, solid solution strengthening and second phase strengthening significantly improves the strength and toughness of medical magnesium alloys.

[0015] In summary, the present invention adds 0.5% to 2% Ca, 0.1% to 0.5% Zn, 0.1% to 0.35% Cu and 0.01% to 0.05% Mo to the magnesium alloy, which not only ensures that the type and content of the added alloying elements are non-toxic to cells, but also has antibacterial and healing effects to a certain extent. At the same time, the alloying elements synergize through fine grain strengthening, solid solution strengthening and second phase strengthening, and the strength and toughness of the medical magnesium alloy are significantly improved. More importantly, MgMoO4 with high thermal stability and water solubility with a melting point of 1060°C is introduced into the magnesium alloy through the laser selective melting process, and the "autosecreting" MoO4 2-The corrosion-resistant protective film formed by the enrichment of ion precipitation on the surface of magnesium alloy has a significant effect on the degradation rate of magnesium alloy. With the increase of MgMoO4 addition, the uniform, dense and stable molybdate precipitant protective film formed becomes thicker and the degradation rate of magnesium alloy becomes lower, thereby achieving the regulation of the degradation rate of magnesium alloy. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 This is a scanning electron microscope morphology image of the spherical atomized magnesium alloy powder in Example 1 magnified 200 times;

[0017] Figure 2 This is a scanning electron microscope morphology image of the spherical atomized magnesium alloy powder particles in Example 1 magnified 2000 times;

[0018] Figure 3 Figure 2 is the corrosion appearance of the magnesium alloy specimens in Example 2 (left) and the comparative example (right) after a standard immersion test in SBF simulated body fluid at 37±0.5°C for 28 days (the immersion test measures the average annual corrosion rate according to ASTM G31-72 standard, and the SBF simulated body fluid ratio is as follows: 5.40NaCl+0.74NaHCO3+2.05Na2CO3+0.22KCl+0.23K2HPO4·3H2O+0.31MgCl2·6H2O+0.29CaCl2+0.07Na2SO4+11.93HEPES);

[0019] Figure 4 This is a scanning electron microscope analysis image of the surface protective film of the magnesium alloy sample immersed for 28 days in Example 2. DETAILED DESCRIPTION

[0020] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments.

[0021] In the following embodiments of the present invention, the induction melting furnace used is composed of a melting power supply, an induction coil, a melting crucible, etc., and is located together with the tundish in a closed circular melting furnace body, and the furnace body is provided with vacuum and gas filling pipeline interfaces. The induction melting furnace and atomizer used in the present invention are both within the scope of the prior art.

[0022] Example 1

[0023] According to the weight ratio of Mg: Ca: Zn: Cu=99.3: 0.5: 0.1: 0.1, weigh the raw materials of magnesium block, calcium block, zinc block and copper wire with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.0×10 5Pa pressure Ar gas, heated to 680℃ under Ar gas protection for smelting, to obtain MgCa 0.5 Zn 0.1 Cu 0.1 The alloy melt is poured into a tundish with a φ5 mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, 3 MPa high-pressure argon gas is opened to carry MgMoO4 particles with a particle size of 1 to 3 μm and spray out from the annular gap of the atomizer nozzle, and the alloy melt flowing out of the leak hole of the tundish is subjected to gas-solid two-phase flow atomization to obtain spherical magnesium alloy powder with MgMoO4 particles with a particle size of 1 to 3 μm attached to the surface. Figure 1 and Figure 2 As shown in the figure, the particle size of magnesium alloy powder is 13~52μm, the atomizer used is a tightly coupled annular gap nozzle, and the argon flow rate is 6.5m 3 / min, MgMoO4 powder flow rate is 3.8mg / s, atomization time is 40min, and the proportion of MgMoO4 in MgCa is controlled 0.5 Zn 0.1 Cu 0.1 The magnesium alloy powder is used in the laser selective melting process for additive manufacturing as follows: the laser power is 150W, the laser spot diameter is 40μm, the scanning speed is 250mm / s, the layer thickness is 15μm, the scanning spacing is 40μm, and the interlayer rotation angle is 67°; the magnesium alloy obtained by the laser selective melting process has a yield strength of 235MPa and an elongation of 21.4%. When immersed in SBF simulated body fluid, it "self-secretes" MoO4 2- The ions are precipitated on the surface of the sample to form a corrosion-resistant protective film to achieve "self-healing". The average corrosion rate in 28 days is 0.1 mm / y. It is used to prepare degradable medical implants. The degradable medical implants include: bone nails, bone plates, bone filling devices, vascular stents, bile duct stents, urethral stents, and tracheal stents. Example 2

[0024] According to the weight ratio of Mg: Ca: Zn: Cu = 98.25: 1.25: 0.3: 0.2, weigh the raw materials of magnesium block, calcium block, zinc block and copper wire with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.1×10 5 Pa pressure Ar gas, heated to 720℃ under Ar gas protection for smelting, to obtain MgCa 1.25 Zn 0.3 Cu 0.2Alloy melt; pour the prepared alloy melt into a tundish with a φ5mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, open 2MPa high-pressure argon gas to carry MgMoO4 particles with a particle size of 1~3μm and spray them out from the annular gap of the atomizer nozzle, and perform gas-solid two-phase flow atomization on the alloy melt flowing out of the leak hole of the tundish to obtain spherical magnesium alloy powder with MgMoO4 particles with a particle size of 1~3μm on the surface. The particle size of the prepared magnesium alloy powder is 13~52μm. The atomizer used is a tightly coupled annular gap nozzle, and the argon gas flow rate is 5m 3 / min, MgMoO4 powder flow rate is 2.5mg / s, atomization time is 35min, and the proportion of MgMoO4 in MgCa is controlled 1.25 Zn 0.3 Cu 0.2 The magnesium alloy powder was used in the laser selective melting process for additive manufacturing as follows: laser power of 300W, laser spot diameter of 50μm, scanning speed of 400mm / s, layer thickness of 20μm, scanning spacing of 60μm, and interlayer rotation angle of 67°; the yield strength of the magnesium alloy obtained by the laser selective melting process was 252MPa, and the elongation was 18.2%. When immersed in SBF simulated body fluid, it "auto-secreted" MoO4 2- The ions are deposited on the surface of the sample to form a corrosion-resistant protective film to achieve "self-healing". The average corrosion rate in 28 days is 0.25 mm / y. It is used to prepare degradable medical implants. The degradable medical implants include: bone nails, bone plates, bone filling devices, vascular stents, bile duct stents, urethral stents, and tracheal stents. Example 3

[0025] According to the weight ratio of Mg: Ca: Zn: Cu = 97.15: 2: 0.5: 0.35, weigh the raw materials of magnesium block, calcium block, zinc block and copper wire with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.2×10 5 Pa pressure Ar gas, heated to 750℃ under Ar gas protection for smelting, to obtain MgCa2Zn 0.5 Cu 0.35 The alloy melt is poured into a tundish with a φ5 mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, 1 MPa high-pressure argon gas is opened to carry MgMoO4 particles with a particle size of 1 to 3 μm and spray out from the annular gap of the atomizer nozzle, and the alloy melt flowing out of the leak hole of the tundish is subjected to gas-solid two-phase flow atomization to obtain spherical magnesium alloy powder with MgMoO4 particles with a particle size of 1 to 3 μm attached to the surface. Figure 1As shown in the figure, the particle size of the magnesium alloy powder is 13~52μm, the atomizer used is a tightly coupled annular gap nozzle, and the argon flow rate is 3m 3 / min, MgMoO4 powder flow rate is 1.4mg / s, atomization time is 30min, and the proportion of MgMoO4 in MgCa2Zn 0.5 Cu 0.35 The magnesium alloy powder is used in the laser selective melting process for additive manufacturing as follows: the laser power is 400W, the laser spot diameter is 70μm, the scanning speed is 500mm / s, the layer thickness is 25μm, the scanning spacing is 70μm, and the interlayer rotation angle is 67°; the magnesium alloy obtained by the laser selective melting process has a yield strength of 268MPa and an elongation of 13.5%. When immersed in SBF simulated body fluid, it "self-secretes" MoO4 2- The ions are deposited on the surface of the sample to form a corrosion-resistant protective film to achieve "self-healing". The average corrosion rate in 28 days is 0.4 mm / y. It is used to prepare degradable medical implants. The degradable medical implants include: bone nails, bone plates, bone filling devices, vascular stents, bile duct stents, urethral stents, and tracheal stents. Comparative Example

[0026] According to the weight ratio of Mg: Ca: Zn: Cu = 98.25: 1.25: 0.3: 0.2, weigh the raw materials of magnesium block, calcium block, zinc block and copper wire with a purity of 99%. After loading, close the door of the induction melting furnace and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.1×10 5 Pa pressure Ar gas, heated to 720℃ under Ar gas protection for smelting, to obtain MgCa 1.25 Zn 0.3 Cu 0.2 Alloy melt; the prepared alloy melt is poured into a tundish with a φ5mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, 2MPa high-pressure argon gas is opened to spray from the annular gap of the atomizer nozzle, and the alloy melt flowing out of the leak hole of the tundish is gas-atomized to obtain spherical magnesium alloy powder. The particle size of the prepared magnesium alloy powder is 13~52μm. The atomizer used is a tightly coupled annular gap nozzle, and the argon gas flow rate is 5m 3 / min, and the atomization time is 35min. The laser selective melting process of the magnesium alloy powder used in additive manufacturing is as follows: the laser power is 300W, the laser spot diameter is 50μm, the scanning speed is 400mm / s, the layer thickness is 20μm, the scanning spacing is 60μm, and the interlayer rotation angle is 67°; the yield strength of the magnesium alloy obtained by the laser selective melting process is 168MPa, the elongation is 8.3%, and the average corrosion rate is 3.5mm / y after immersion in SBF simulated body fluid for 28 days.

[0027] The analysis of Example 2 and the comparative example shows that by adjusting the amount of MgMoO4 with a melting point of 1060°C, high stability and water solubility, as well as the type and content of alloying elements, the degradation rate and mechanical properties of the magnesium alloy can be effectively regulated. 2- The corrosion-resistant protective film formed by the enrichment of ion precipitation on the surface of the sample has a significant effect on the degradation rate of the magnesium alloy. With the increase of the amount of MgMoO4 added, the uniform, dense and stable molybdate precipitant protective film formed is thicker, and the degradation rate of the magnesium alloy is lower. The corrosion rate of the magnesium alloy sample without MgMoO4 added under the same corrosion conditions is 14 times that of the magnesium alloy sample with MgMoO4 added. Figure 3 The corrosion appearance comparison chart shows that after the magnesium alloy sample with MgMoO4 added was immersed in the SBF simulated body fluid at 37±0.5℃ for 28 days, except for the part where the iron wire hanger was suspended, the magnesium alloy sample basically maintained its bright color before corrosion, while the magnesium alloy sample without MgMoO4 added was rusted after being immersed in the SBF simulated body fluid at 37±0.5℃ for 28 days. Figure 4 Scanning electron microscope analysis found that after immersion corrosion, a protective film with a thickness of about 10μm appeared on the surface of the magnesium alloy sample with MgMoO4 added. The amount of Mo added to the magnesium alloy powder was only 0.03wt.%, but the Mo element in the film layer was significantly enriched to 1.85wt.%, indicating that the protective film formed by the molybdate deposition agent is the key to reducing the degradation rate of the magnesium alloy.

Claims

1. A magnesium alloy powder for additive manufacturing of degradable medical implants, characterized in that: The magnesium alloy powder is composed of MgCa x Zn y Cu z Alloy particles and attached to MgCa x Zn y Cu z The composition of the MgMoO4 particles on the particle surface is, by weight percentage, 0.5%≤x≤2%, 0.1%≤y≤0.5%, 0.1%≤z≤0.35%, and the remainder is Mg. The MgMoO4 accounts for MgCa x Zn y Cu z 0.02% to 0.1% by weight; the MgCa x Zn y Cu z The particles are spherical with a particle size of 13~52μm, and the MgMoO4 particles are spherical with a particle size of 1~3μm.

2. A method for preparing magnesium alloy powder for additive manufacturing of degradable medical implants as claimed in claim 1, characterized in that: The steps include: (1) According to MgCa x Zn y Cu z The raw materials magnesium block, zinc block, calcium block and copper wire are weighed and placed in an induction melting furnace, and melted under the protection of Ar gas to obtain an alloy melt; (2) The alloy melt obtained in step (1) is poured into a tundish with a φ5 mm leak hole at the bottom through a guide tube under the protection of Ar gas, and at the same time, high-pressure argon gas is turned on to carry MgMoO4 particles and sprayed out from the annular gap of the atomizer nozzle, and the alloy melt flowing out of the leak hole of the tundish is subjected to gas-solid two-phase flow atomization to obtain magnesium alloy powder for additive manufacturing of degradable medical implants.

3. The method for preparing magnesium alloy powder for additive manufacturing of degradable medical implants according to claim 2, characterized in that: The pressure range of the protective gas Ar in step (1) is 1.0~1.2×10 5 Pa; the melting temperature range is 680~750℃.

4. The method for preparing magnesium alloy powder for additive manufacturing of degradable medical implants according to claim 2, characterized in that: In step (2), the argon pressure range is 1~3MPa, and the argon flow rate is 3~6.5m 3 / min; the flow rate of MgMoO4 particles is 1.4~3.8mg / s, and the particle size is 1~3μm; the atomization time is 30~40min, and the atomizer used is a tightly coupled annular gap nozzle with an annular gap width of 3mm.

5. A use of the magnesium alloy powder for additive manufacturing of degradable medical implants as claimed in claim 1, characterized in that: The magnesium alloy powder is used in the laser selective melting process in additive manufacturing to prepare degradable medical implants, and the degradable medical implants include: bone nails, bone plates, bone filling devices, vascular stents, bile duct stents, urethral stents, and tracheal stents.

6. A use of the magnesium alloy powder for additive manufacturing of degradable medical implants as claimed in claim 5, characterized in that: The laser selective melting process has a laser power of 150 to 400 W, a laser spot diameter of 40 μm to 70 μm, a scanning speed of 250 to 500 mm / s, a layer thickness of 15 to 25 μm, a scanning spacing of 40 to 70 μm, and an interlayer rotation angle of 67°. The yield strength of the magnesium alloy obtained by the laser selective melting process is 235 MPa to 268 MPa, and the elongation is 13.5% to 21.4%. When the magnesium alloy is immersed in SBF simulated body fluid, the average corrosion rate after immersion for 28 days is 0.1 to 0.4 mm / y.

Citation Information

Patent Citations

  • Mg-Nd-Zr-Sr-Sc-Sm biodegradable magnesium alloy and preparation method thereof

    CN114231811A

  • Anastomosing nail material capable of degrading Mg-Zn-Ca-M in organism, and preparation method thereof

    CN109972007A

  • Low-modulus artificial bone and preparation method thereof

    CN110129642A